New species and new records of Pterosthetops: eumadicolous water beetles of the South African Cape (Coleoptera, Hydraenidae) - Bilton, David T. (Zootaxa, 2014)
Pterosthetops is one of a number of hydraenid genera endemic to the Cape of South Africa, whose minute moss beetle fauna is amongst the most diverse on earth. Here seven species are described as new: Pterosthetops baini sp. nov., Pterosthetops coriaceus sp. nov., Pterosthetops indwei sp. nov., Ptersothetops pulcherrimus sp. nov., Pterosthetops swartbergensis sp. nov., Pterosthetops tuberculatus sp. nov. and Pterosthetops uitkyki sp. nov., all from mountains in the Western Cape region. New collection records are also provided for all five previously described members of the genus, together with a revised key. Pterosthetops appear to be specialist inhabitants of seepages over rock faces (hygropetric/madicolous habitats), rarely being found outside such situations.